Gene Transfer and Expression Protocols - Murray, Edward J.; SpringerLink (Online service) (Totowa, NJ : Humana Press : Imprint: Humana, 1991)
Biology is the study of living things. The classical approach might be described as holistic and descriptive, whereas the modern molecular - proach aims to be investigative, reductionist, and mechanistic . Genes contain all the information for the structure of all living things ; thus, the understanding of how genes are regulated is an important step toward understanding the nature of living things. The study of gene regulation has been made more tractable by the design of simple expe- mental models in which a single gene can be isolated from the milieu of the organism. The new science of molecular biology has introduced techniques that permit the design of such experimental models. In - sence, the genome of the organism is dissected in such a manner that specific genes may now be introduced into an appropriate cell line . Subsequent analysis of the proteins expressed from the genes under study results in the identification of the regulatory DNA sequences .
Preparation of Recombinant Plasmid DNA for DNA-Mediated Gene Transfer -- Calcium Phosphate Mediated Gene Transfer into Established Cell Lines -- Transfection of the ChloramphenicolAcetyltransferase Gene into Eukaryotic Cells Using Diethyl-Aminoethyl (DEAE)-Dextran -- Polybrene/DMSOAssisted Gene Transfer -- Electroporation Technique of DNA Transfection -- Irradiation and Fusion Gene Transfer -- Direct Use of ? Phage Particles for DNA Transfection -- Cationic Liposome-Mediated Transfection with Lipofectin™ Reagent -- Preparation of High-Molecular-Weight DNA for Use in DNA Transfection -- Chromosome-Mediated Gene Thnsfer -- Manipulation of Adenovirus Vectors -- Manipulation of Vaccinia Virus Vectors -- Manipulation of Baculovirus Vectors -- Manipulation of SV40 Vectors -- Choice and Manipulation of Retroviral Vectors -- Use of Tissue-Plasminogen Activator as a Reporter Gene -- Use of Escherichiu coli (E. coli) lacZ (?-Galactosidase) as a Reporter Gene -- Application of the Firefly Luciferase Reporter Gene -- Use of Vectors to Confer Resistance to Antibiotics G418 and Hygromycin in Stably Transfected Cell Lines -- Selection of Cells Defective in Pyrimidine (TK?) and Purine (APRT? and HPRT? Salvage -- Quantitative and Qualitative Analysis of Exogenous Gene Expression by the S1 Nuclease ProtectionAssay -- The RNase Protection Assay -- Primer Extension Analysis of mRNA Isolated from Transfected Cell Lines -- Northern Blot Analysis of Gene Expression -- Analysis of Transcriptional Initiation in Isolated Nuclei -- Immunoperoxidase Staining of Gene Products in Cultured Cells Using Monoclonal Antibodies -- The Use of Flow Cytometry to Detect Transfected Gene Products -- Determination of Foreign Gene Copy Number in Stably Transfected Cell Lines by Southern Transfer Analysis -- Evaluation of Extrachromosomal Gene Copy Number of Transiently Transfected Cell Lines -- Use of Dpn I Restriction Enzyme to Assess Newly Replicated Gene Copies in Amplifiable Vector Systems -- Use of Polymerase Chain Reaction (PCR) to Detect Homologous Recombination in Transfected Cell Lines -- Induction of Erythroid-Specific Expression in Murine Erythroleukemia (MEL) Cell Lines.
Keywords: Human genetics; Human Genetics